2019
DOI: 10.3390/ejihpe10010005
|View full text |Cite
|
Sign up to set email alerts
|

Improving Employee Performance in Industrial Parks: An Empirical Case of Garment Enterprises in Binh Duong Province, Vietnam

Abstract: In responding to the current international integration and fierce competition on marketplace, over the last few decades, most businesses have tried to continuously improve their performance for better competitiveness. One of the preferred approaches is to enhance their employee performance; thus, fully capturing its determinants is critical. Thus, this study aimed at identifying key factors affecting employee performance so that businesses can create proper policies and actions to improve their overall perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Based on this, the study concluded that human resource accounting had a positive significant effect on organizational productivity of the listed sampled manufacturing companies in Nigeria. The findings of this study related to the outcome of the previous studies conducted by Esfahani et al (2017) which opined that employees' benefits enhances productivity and organizational performance; Nguyen and Giang (2019) on Vietnam firms found that reward appreciation, employee development and training, employee benefits, and adequate employee motivation had a positive significant effect on organizational performance; Yoopetch et al (2021) who found that employees' satisfaction and productivity positively affect corporate performance Fatima and Olaore (2021) who reported positive effect, On the contrary, other prior studies have found contradictory results. For instance, the studies of Khan (2021) reported negative effect and the study by Imran et al (2018) equally reported negative effect.…”
Section: Discussion Of Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…Based on this, the study concluded that human resource accounting had a positive significant effect on organizational productivity of the listed sampled manufacturing companies in Nigeria. The findings of this study related to the outcome of the previous studies conducted by Esfahani et al (2017) which opined that employees' benefits enhances productivity and organizational performance; Nguyen and Giang (2019) on Vietnam firms found that reward appreciation, employee development and training, employee benefits, and adequate employee motivation had a positive significant effect on organizational performance; Yoopetch et al (2021) who found that employees' satisfaction and productivity positively affect corporate performance Fatima and Olaore (2021) who reported positive effect, On the contrary, other prior studies have found contradictory results. For instance, the studies of Khan (2021) reported negative effect and the study by Imran et al (2018) equally reported negative effect.…”
Section: Discussion Of Findingssupporting
confidence: 65%
“…While there exist vast studies that have researched organizational productivity, yet, there is a dearth of studies that had considered attempting the problem of organizational productivity from the perspective of human resource accounting, creating a gap in the literature. For instance, Fatima and Olaore (2021) and Nguyen and Giang (2019) in separate studies found positive effects, on the contrary, Imran, Ilyas, Aslam, and Fatima (2018) and Khan (2021) documented negative effect. The divergent opinions and mixed results equally suggest inconsistences, unresolved problems, demanding for further studies.…”
Section: Introductionmentioning
confidence: 94%
“…Heavy workload is one of the major contributing factors to employees’ overtime work, usually related to short working hours, heavy workloads, and high work requirements. As far as employees are concerned, overtime work caused by workload can be regarded as poor performance ( Nguyen and Giang, 2020 ), making them feel controlled and emotionally negative ( Laurence et al, 2016 ), and thus even leading to burnout ( Ko and Choi, 2018 ) and causing a sense of deprivation ( Chen et al, 2020 ).…”
Section: Literature Review and Research Designmentioning
confidence: 99%
“…Whether overtime work has a positive effect on corporate organizational performance is still controversial ( Ko and Choi, 2018 ; Nguyen and Giang, 2020 ). However, the effect and impact of overtime on employees are relatively consistent, such as reducing life well-being; increasing psychological pressure ( Rose, 1995 ); and causing sleep disorders, high blood pressure, and other diseases ( Harma, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the World Health Organization (2014) indicates that availability of the health workers relates to the sufficiency of the healthcare workers with the requisite skills to serve the population under their jurisdiction. The accessibility characteristics of the health worker relate to the equitable access to health workers amongst the populace requiring their expertise (Nguyen & Giang, 2019). On the other hand, acceptability relates to the manner in which they treat their patients with dignity creating provision development of trust aspects in healthcare provision (World Health Organization, 2014).…”
Section: Introductionmentioning
confidence: 99%